Introduction: Open Data and Africa - Leonelli, S; Rappert, B; Bezuidenhout, L (Ubiquity Press, 2019)
This introduction outlines the contents of the special collection “Open Data and Africa”, which documents the goals and aspirations associated with Open Data means in Africa today: what opportunities they offer, what challenges they pose and what the implications follow from the increasing political and institutional support for this concept.